The polymorphism analysis and therapy vaccine target epitopes screening of HPV-35 E6 E7 among the threaten [alpha]-9 HPV in Sichuan area - He, Jiaoyu; Li, Tianjun; Cheng, Chunlan; Li, Ning; Gao, Peng; Lei, Dan; Liang, Rong; Ding, Xianping (Virology journal, 2024)
High-risk human papilloma virus (HR-HPV) persistent infection is closely associated with the development of cervical cancer and squamous intraepithelial lesion (SIL).The [alpha]-9 HPVs, which is predominantly composed of HR-HPV types, account for 75% of HR-HPV infection in Sichuan. The oncoproteins E6 and E7 of HPV play a crucial role in tumor initiation and progression. Notably, HPV-35 is the only HR-HPV type within the [alpha]-9 genus that is not included in the nine-valent HPV prophylactic vaccine. Cervical cell samples obtained from Sichuan were collected for HPV detection and genotyping. Among the 406 HPV-positive samples, 31 HPV-35 were detected, 24 HPV-35 E6 and 26 E7 were successfully amplified and sequenced, five nucleotide mutations in E6 and three in E7 were detected, T232C, T434G of E6 (W78R, I145R) and C67T, G84T of E7 (H23Y, L28F) were non-synonymy mutation. PAML 4.8 server was used to detect positive selection sites of HPV-35 E6, E7, and E6 is W78R. Phyre2 were used to predict and analyze protein structures, W78R made influences on protein structure. IEDB were used to screen epitopes vaccine target for HPV-35 affection therapy, and 5 HPV-35 E6 and 3 HPV-35 E7 most potential epitopes were obtained, the most potential peptides for therapy vaccine design were 79-91YRYSVYGETLEKQ, 45-60FACYDLCIVREGQPY, 124-135RFHNIGGRWTGR of E6; 3-19GEITTLQDYVLDLEPEA, 38-47TIDGPAGQAK, 70-88VQSTHIDIRKLEDLLMGTF of E7 and W78R mainly decreased the epitopes affinity.